Effects of exposure to prothioconazole and its metabolite prothioconazole-desthio on oxidative stress and metabolic profiles of liver and kidney tissues in male mice. (15th January 2021) - Meng, Zhiyuan; Tian, Sinuo; Sun, Wei; Liu, Li; Yan, Sen; Huang, Shiran; Zhu, Wentao; Zhou, Zhiqiang
Abstract: Prothioconazole (PTC), a popular agricultural fungicide, and its main metabolite prothioconazole-desthio (PTCd) are receiving great attention due to their toxicological effects in the non-target organisms. This study investigated their dosage-dependent (1 and 5 mg/kg BW/day) toxicological effects on oxidative stress and metabolic profiles of liver and kidney tissues using male mice. PTC and PTCd significantly inhibited the growth phenotype including body weights gain, liver and kidney indices. Furthermore, these effects were deeply investigated using the biomarkers of oxidative stress, and metabolomics. Notably, these effects were dose and tissue-dependent. Specifically, the more serious impacts involving oxidative stress and metabolic disorders were observed in the high concentration treatment groups. Also, the liver tissue was more severely affected than the kidney tissue. Lastly, the change in oxidative stress biomarkers and metabolomics profile revealed that PTCd induced more severe toxic effects than the parent compound PTC. In brief, these results indicate that exposure to PTC and PTCd could cause potential health risks in mammals. Graphical abstract: Image 1 Highlights: The toxicological effects of PTC and PTCd were studied in male mice. Changes in the oxidative stress markers and metabolomics were examined. These effects were dose and tissue-dependent. The liver was more affected than the kidney. PTCd caused more serious toxicological effects than PTC. Abstract : Capsule: Toxicological effects of PTC and PTCd on oxidative stress and metabolic profiles of liver and kidney tissues were investigated in male mice.